Driving a positive brand image to customers through strategic corporate social responsibility: The case of deposit money banks in Nigeria - Dudutari, Bereprebofa; Francis, Ndudi; Ifeanyi, Aloamaka Judith (International journal of economic perspectives, 2022)
This study examined the impact of corporate social responsibilities (CSR) on the brand image with emphasis on deposit money banks in Asaba, Delta State. The study aimed at determining how banks' engagement in CSR practices affects customers' perception of banks' brand image. To achieve this objective, a sample of 396 respondents was randomly drawn from twelve (12) branches of four (4) deposit money banks including Access Bank Plc., Fidelity Bank Plc., GTB Plc., and Zenith Bank Plc. We considered such CSR metrics as philanthropic responsibilities, sustainability responsibilities and ethical responsibilities; while the brand image was measured by customers' perception of brand attributes and benefits. The multiple regression estimation techniques were employed for data analysis and the test was carried out using the statistical package for social sciences (SPSS). The result revealed that all corporate social responsibility metrics have a positive and significant impact on the brand image of the selected banks. The implication is that banks' engagement in CSR practices significantly impacts customers' perception of the banks' brand.